Selfing and Outcrossing Fertility in Common Bermudagrass under Open‐Pollinating Conditions Examined by SSR Markers. Issue 4 (1st July 2014) - Tan, Chengcheng; Wu, Yanqi; Taliaferro, Charles M.; Bell, Greg E.; Martin, Dennis L.; Smith, Mike W.; Moss, Justin Q.
ABSTRACT: C. dactylon (L.) Pers. var. dactylon is a cosmopolitan grass species with significant economic value for turf, forage, and soil conservation in the southern United States. The species has long been characterized as an outcrossing species based on heterogeneity of natural populations, comparison of seed set rates under self‐ and cross‐pollination, and assumption of widespread self‐incompatibility. However, reproductive behavior of plants in breeding populations based on definitive characterization of their progeny as to self‐ or cross‐pollinated origin is not available. The objective of this experiment was to quantify selfing and outcrossing rates of common bermudagrass plants grown in field environments conducive to interbreeding. Twenty‐five clonal common bermudagrass plants grown at Stillwater and Perkins, OK in a randomized complete block design with three replications were used in the study. Ten progeny from open‐pollinated seed harvested from each field plot of the maternal plants were grown in a greenhouse at the Agronomy Research Station, Oklahoma State University. Plant DNA samples were isolated from 1439 progeny from both sites along with the 25 seed parents. Eleven polymorphic simple sequence repeat (SSR) markers were chosen to identify breeding origin of the progeny by comparing SSR marker genotypes of the progeny with their respective maternal parents. Among the progeny examined, only two progeny plants from accessions A12281 and A12363 were identified to be selfed, indicating an extremely high outcrossing rate of 99.86%. The finding of complete or near complete outcrossing behavior in this experiment should assist in a fuller understanding of the sexual reproduction characteristics of common bermudagrass.